Antipyretic Effect of Ketoprofen - Celebi, S.; Hacimustafaoglu, M.; Aygun, D.; Arisoy, E. S.; Karali, Y.; Akgoz, S.; Seringec, M. (Springer India, 2009)
Objective. To investigate the efficacy and side effect of ketoprofen as well as compliance with respect to the taste of the drug and compare these parameters with those of acetaminophen and ibuprofen. Methods. A total of 301 patients between 1-14 years of age who attended to emergency rooms of three medical centers with the complaint of fever that required antipyretic therapy were included in the study. Fever was measured with the aid of a tympanic thermometer (Braun Kronberg 6014) and followed for 4-6 hours. The measurement was repeated at 30, 60, 120 minutes, and again 4-6 hours after the initial assessment. Results. The mean age of the patients was 47.8 +/- 41.1 months. The patients randomly received 15 mg/kg/dose of acetaminophen (n=112 group 1), 0.5 mg/kg/dose of ketoprofen (n=105, group 2), or 10 mg/kg/dose of ibuprofen (n=84, group 3). Temperature records in three groups was 38.4 +/- 0.7 degrees C, 38.4 +/- 0.7 degrees C, and 38.5 +/- 0.5 degrees C at 30 minutes; 38.0 +/- 0.7 degrees C, 37.9 +/- 0.7 degrees C, and 38.0 +/- 0.6 degrees C at 60 minutes (p > 0.05), 37.7 +/- 0.6 degrees C, 37.6 +/- 0.7 degrees C, and 37.7 +/- 0.5 degrees C at 120 minutes (p > 0.05); 37.5 +/- 0.7 degrees C, 37.3 +/- 0.6 degrees C, and 37.4 +/- 0.6 degrees C at 4-6 hours after admission (P > 0.05) respectively. The fever was significantly lower at 30, 60, and 120 minutes in all groups (p < 0.05) respectively. Early vomiting after medication (< 6 hours) was observed in 3.8%, 13.5%, and 9.6% respectively whereas late vomiting (6-48 hours) occurred in 1.3%, 2.7%, and 5.8% respectively (p > 0.05). Bad taste was expressed by 5.1%, 12.2%, and 5.8% early (< 6 hours), and 3.9%, 8.1%, and 3.8% late (6-48 hours) (p > 0.05). There were no differences between age groups for antipyretic effect, taste and adverse effect in three drugs (p > 0.05). Conclusion. All three drugs were similar in terms of efficacy, adverse effects, and compliance within 48 hours of therapy. These results suggest that ketoprofen may be used for antipyresis as an alternative to acetaminophen and ibuprofen. [Indian J Pediatr 2009; 76 (3) : 287-291] E-mail : solmaz@uludag.edu.tr
Keywords: Fever; Ketoprofen; Acetaminophen; Ibuprofen; Children